Role of Elongin BC-containing ubiquitin ligases - Okumura, Fumihiko; Nakatsukasa, Kunio; Kamura, Takumi (Frontiers in Oncology, 2012)
The Elongin complex was originally identified as a positive regulator of RNA polymerase II and is composed of a transcriptionally active subunit (A) and two regulatory subunits (B and C). The Elongin BC complex enhances the transcriptional activity of Elongin A. “Classical” SOCS box-containing proteins interact with the Elongin BC complex and have ubiquitin ligase activity. They also interact with the scaffold protein Cullin (Cul) and the RING domain protein Rbx and thereby are members of the Cullin RING ligase (CRL) superfamily. The Elongin BC complex acts as an adaptor connecting Cul and SOCS box proteins. Recently, it was demonstrated that classical SOCS box proteins can be further divided into two groups, Cul2- and Cul5-type proteins. The classical SOCS box-containing protein pVHL is now classified as a Cul2-type protein. The Elongin BC complex containing CRL family is now considered two distinct protein assemblies, which play an important role in regulating a variety of cellular processes such as tumorigenesis, signal transduction, cell motility, and differentiation.